2023
DOI: 10.2106/jbjs.23.00092
|View full text |Cite
|
Sign up to set email alerts
|

Is Elective Total Hip Arthroplasty Safe in Nonagenarians?

Vincent J. Leopold,
Paula Krull,
Sebastian Hardt
et al.

Abstract: Background: An increasing number of elderly patients are becoming candidates for elective total hip arthroplasty (THA). Conflicting results exist with regard to the safety of THA in nonagenarians. The aims of this study were to evaluate postoperative mortality and morbidity after THA in nonagenarians and underlying risk factors. We hypothesized that nonagenarians undergoing elective THA would show higher morbidity than younger patients and higher mortality than nonagenarians in the general populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…A recent study showed that the mortality rates in patients aged > 90 years undergoing THA were lower than those in a corresponding age group of the general population, emphasizing the safety of THA. 31 Other studies confirmed similar early mortality rates for cemented and uncemented designs of stem, especially if the cohort of patients is for covariates. 15,32 The increased rates of mortality for cemented designs of stem, which have been described in the past, might be the result of a bias in the selection of patients and persistent confounding factors, rather than the type of fixation.…”
Section: Time Of Deathmentioning
confidence: 61%
“…A recent study showed that the mortality rates in patients aged > 90 years undergoing THA were lower than those in a corresponding age group of the general population, emphasizing the safety of THA. 31 Other studies confirmed similar early mortality rates for cemented and uncemented designs of stem, especially if the cohort of patients is for covariates. 15,32 The increased rates of mortality for cemented designs of stem, which have been described in the past, might be the result of a bias in the selection of patients and persistent confounding factors, rather than the type of fixation.…”
Section: Time Of Deathmentioning
confidence: 61%
“…This study from Berlin (Germany) aimed to evaluate postoperative morbidity and mortality rates in nonagenarians undergoing elective THA and to identify associated risk factors. 5 The hypothesis tested was that nonagenarians would experience higher morbidity and mortality when compared to both younger patients and their nonagenarian counterparts in the general population. The authors reported their observational cohort study using data from the German Arthroplasty Registry.…”
Section: Hip Replacement Into Your Ninetiesmentioning
confidence: 99%
“…Health inequities pertaining to age are, however, ubiquitous and have been extensively documented. [2][3][4][5][6][7] A recent study 8 established that even among patients older than 90 years, elective total hip replacement (due to osteoarthritis) may be appropriately considered, if patients are carefully selected. Another recent study 9 recommended that, despite higher mortality compared with younger groups, nonagenarian patients should not be denied total hip replacement.…”
Section: Introductionmentioning
confidence: 99%